THE CRITICAL ANALYSIS OF THE CAUSES OF POLITICAL INSTABILITY IN PAKISTAN FROM 1988 TO 1999 (SPECIAL REFERENCE TO SINDH PROVINCE) - Siyal, Nazir (Journal of Arts & Social Sciences, 2021)
This research article’s primary goal is to determine the triggers and implications of Pakistan’s political instability and its effects on the political situation of Sindh during the democratic decade from 1988 to 1999. Despite abundant natural resources, Pakistan is one of the only countries where political unrest has severely hampered the social and political development of the country. So, this paper aims to understand the leading factors of political instability that weakened the country’s political growth and led the nation in general and Sindh province, in particular, to suffer social and ethnic problems in society. To understand the issue deeply, the researcher used unstructured Interviews as a research tool with law-makers, academicians, and political scientists. However, many interviewees accepted that the lack of enthusiastic leadership, the Role of the weak judiciary, the passive role of civil bureaucracy, and political ethnicity had been the leading factors for political and social unrest. Thus, the study’s findings would help the law-makers and academicians of different colleges and universities to design their policies and curriculum. Additionally, this paper would help various nationalists and political parties of Sindh province to comprehend the genuine reasons for unrest in the area from 1988 to 1999.Key Words:  Political instability, Weak Judiciary, Political ethnicity, Foreign interference, Role of civil bureaucracy